Backlighting the European Indium Recycling Potentials. (13th March 2018) - Ciacci, Luca; Werner, Tim T.; Vassura, Ivano; Passarini, Fabrizio
Summary: With increased understanding of the effects of human activities on the environment and added awareness of the increasing societal value of natural resources, researchers have begun to focus on the characterization of elemental cycles. Indium has captured significant attention due to the potential for supply shortages and nonexistent recycling at end of life. Such a combination of potentially critical features is magnified for countries that depend on imports of indium, notably many European countries. With the aims of analyzing the dynamics of material flows and of estimating the magnitude of secondary indium sources available for recycling, the anthropogenic indium cycle in Europe has been investigated by material flow analysis. The results showed that the region is a major consumer of finished goods containing indium, and the cumulative addition of indium in urban mines was estimated at about 500 tonnes of indium. We discuss these results from the perspective of closing the metal cycle in the region. Securing access to critical raw materials is a priority for Europe, but the preference for recycling metal urban mines risks to remain only theoretical for indium unless innovations in waste collection and processing unlock the development of technologies that are economically feasible and environmentally sustainable.